Higher NICU admissions in infants born at ≥35 weeks gestational age during the COVID-19 pandemic - Jegatheesan, Priya; Narasimhan, Sudha Rani; Huang, Angela; Nudelman, Matthew; Song, Dongli (Frontiers in Pediatrics, 2023)
Background Increasing evidence has shown that the COVID-19 pandemic has had a profound negative impact on vulnerable populations and a significant effect on maternal and neonatal health. We observed an increase in the percentage of infants admitted to NICU from 8% to 10% in the first year of the pandemic. This study aimed to compare the delivery room outcomes, NICU admissions and interventions, and neonatal outcomes two years before and during the pandemic. Methods This was a retrospective study in a public hospital between pre-COVID-19 (April 2018–December 2019) and COVID-19 (April 2020–December 2021). Data were obtained from all live births at ≥35 weeks gestation (GA). Maternal and neonatal demographics, delivery room (DR), and NICU neonatal outcomes were compared between the study periods using simple bivariable generalized estimating equations (GEE) regression. Multivariable GEE logistic regression analysis was performed to adjust for the effects of baseline differences in demographics on the outcomes. Results A total of 9,632 infants were born ≥35 weeks gestation during the study period (pre-COVID-19 n = 4,967, COVID-19 n = 4,665). During the COVID-19 period, there was a small but significant decrease in birth weight (33 g); increases in maternal diabetes (3.3%), hypertension (4.1%), and Hispanic ethnicity (4.7%). There was a decrease in infants who received three minutes (78.1% vs. 70.3%, p < 0.001) of delayed cord clamping and increases in the exclusive breastfeeding rate (65.9% vs. 70.1%, p < 0.001), metabolic acidosis (0.7% vs. 1.2%, p = 0.02), NICU admission (5.1% vs. 6.4%, p = 0.009), antibiotic (0.7% vs. 1.7%, p < 0.001), and nasal CPAP (1.2% vs. 1.8%, p = 0.02) use. NICU admissions and nasal CPAP were not significantly increased after adjusting for GA, maternal diabetes, and hypertension; however, other differences remained significant. Maternal hypertension was an independent risk factor for all these outcomes. Conclusion During the COVID-19 pandemic period, we observed a significant increase in maternal morbidities, exclusive breastfeeding, and NICU admissions in infants born at ≥35 weeks gestation. The increase in NICU admission during the COVID-19 pandemic was explained by maternal hypertension, but other adverse neonatal outcomes were only partly explained by maternal hypertension. Socio-economic factors and other social determinants of health need to be further explored to understand the full impact on neonatal outcomes.